Patient-Reported Expedited Partner Therapy for Gonorrhea in the United States. Issue 9 (September 2015) - Stenger, Mark R.; Kerani, Roxanne P.; Bauer, Heidi M.; Burghardt, Nicole; Anschuetz, Greta L.; Klingler, Ellen; Schumacher, Christina M.; Simon, Julie; Golden, Matthew
<x xml:space="preserve">Abstract</x> Background Expedited partner therapy (EPT) has been shown to prevent reinfection in persons with gonorrhea and to plausibly reduce incidence. The Centers for Disease Control and Prevention recommends EPT as an option for treating sex partners of heterosexual patients. Few studies that examine how the reported use of this valuable intervention differs by patient and provider characteristics and by geography across multiple jurisdictions in the United States are currently available. Methods Case and patient interview data were obtained for a random sample of reported cases from 7 geographically disparate US jurisdictions participating in the Sexually Transmitted Disease (STD) Surveillance Network. These data were weighted to be representative of all reported gonorrhea cases in the 7 study sites. Patient receipt of EPT was estimated, and multivariate models were constructed separately to examine factors associated with receipt of EPT for heterosexuals and for men who have sex with men. Results Overall, 5.4% of patients diagnosed and reported as having gonorrhea reported receiving EPT to treat their sex partners. Heterosexual patients were more likely to have received EPT than men who have sex with men at 6.6% and 2.6% of patients, respectively. Receipt of EPT did not vary significantly by race, Hispanic ethnicity, or age for either group, although significant variation was observed in different provider settings, with patients from family planning/reproductive health and STD clinic settings more likely to report receiving EPT. Jurisdiction variations were also observed with heterosexual patients in Washington State most likely (35.5%), and those in New York City, Connecticut, and Philadelphia least likely to report receiving EPT (<2%). Conclusions With the exception of one jurisdiction in the STD Surveillance Network actively promoting EPT use, patient-reported receipt of the intervention remains suboptimal across the network. Additional efforts to promote EPT, especially for patients diagnosed in private provider and hospital settings, are needed to realize the full potential of this valuable gonorrhea control intervention.